Silver fir restitution: The role of seedling stock type in adapting to various environmental conditions - Wojciech Kowalkowski; Radosław Jagiełło; Marlena Baranowska; Wladysław Barzdajn (Journal of Forest Science)
Due to past human activities, Abies alba Mill. (European silver fir) now covers only 0.7% of the forest area in the Sudety Mountains. A large-scale restitution program has been launched to produce, plant, and effectively protect over 200 million seedlings. This study aims to validate commonly used seedling stock types and provide critical insights into identifying the most effective one. Three-year-old bareroot seedlings were produced in the open-canopy nursery (3/0) or under-canopy nurseries in Scots pine (Pinus sylvestris L.) (3/0 Sp) or Norway spruce [Picea abies (L.) H. Karst] (3/0 Ns) stands. Two stocks were produced in a greenhouse and transplanted to an open-canopy nursery (2/1) after the second year or into containers designed by Kosterkiewicz (2/1 K). Seedlings have been planted in four regions in the Sudety Mountains. Two performance characteristics have been measured: height and survival rate. Our findings demonstrate a clear gradient in sapling performance among seedling stock types (survival rate): 2/1 K (81%), 3/0 (73%), 3/0 Sp (73%), 2/1 (70%), 3/0 Ns (62%). This paper has shown that under favourable environmental conditions, bareroot seedlings can sufficiently achieve stable regeneration. Containerised seedlings perform better in harsher and more challenging microclimatic or trophic conditions. Kosterkiewicz's method presents a relatively low-cost and environmentally friendly alternative for silver fir restitution.